2010
DOI: 10.1097/ftd.0b013e3181fa97cc
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CYP2C9 Genetic Polymorphism and Undernourishment on Plasma-Free Phenytoin Concentrations in Epileptic Patients

Abstract: The objective of this study was to study the effect of CYP2C9 genetic polymorphism and undernourishment on free phenytoin concentrations in epileptic patients. The study was done in 70 patients who were taking phenytoin therapy for the treatment of epileptic seizures. Genotyping of CYP2C9 (*2 and *3) was determined by the polymerase chain reaction-restriction fragment length polymorphism method. Bound and free plasma phenytoin was separated using equilibrium dialysis technique. Total and free phenytoin concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…44 Several studies have reported the influence of CYP2C9*2, CYP2C9*3, CYP2C19 *2 and CYP2C19*3 variants on PHT pharmacokinetics. 5,8,9,24,[45][46][47] In contrast, we did not find an association between CYP2C9 (*2, *3) and CYP2C19 (*2, *3) alleles and PHT plasma concentration, supporting the report by Taguchi and colleagues. 10 However, our observation could be owing to the low frequency of these alleles found among MM patients coupled with our small sample size.…”
Section: Discussioncontrasting
confidence: 60%
“…44 Several studies have reported the influence of CYP2C9*2, CYP2C9*3, CYP2C19 *2 and CYP2C19*3 variants on PHT pharmacokinetics. 5,8,9,24,[45][46][47] In contrast, we did not find an association between CYP2C9 (*2, *3) and CYP2C19 (*2, *3) alleles and PHT plasma concentration, supporting the report by Taguchi and colleagues. 10 However, our observation could be owing to the low frequency of these alleles found among MM patients coupled with our small sample size.…”
Section: Discussioncontrasting
confidence: 60%
“…CYP2C9*3 (rs1057910 A > C) is associated with decreased metabolism of phenytoin in vitro and in vivo in pharmacokinetic studies of epileptic patients [4,9,27]. CYP2C9*3 is also associated with increased dose in patients with epilepsy [28].…”
Section: Pharmacogenomicsmentioning
confidence: 99%
“…An A > C transversion at the base pair 1075 in exon 7 (rs 1057910) that results in an isoleucine to leucine change at the codon 359 (Ile359Leu), defines the allelic variant CYP2C9*3 [3,8,9,10,11,12]. On the other hand, the polymorphic isoforms CYP2C19*2 and CYP2C19*3 are caused by a G > A transition at the base pairs 681 in exon 5 (rs 4244285) and 683 in exon 4 (rs 4986893), respectively.…”
Section: Introductionmentioning
confidence: 99%